Fungsi Bagas Godang dan Sopo Godang sebagai Media Pendidikan Nilai dan Moral pada Generasi Muda Mandailing - Nuratikah; Manna Khoiri; Rosdelima Rangkuti; Dina Astika Siregar; Nur Azizah; Rahmi Wahyuni (Sujud: Jurnal Agama, Sosial dan Budaya, 2026)
This study aims to examine and analyze the role of Bagas Godang and Sopo Godang as instruments for moral and value education among Mandailing youth in the effort to preserve local wisdom and shape the character of the next generation. The background of this research stems from the declining understanding of young generations toward the noble values of Mandailing customs, particularly those reflected in the social system and traditional architecture of these two structures. The study employs a qualitative descriptive approach, with data collected through field observations, in-depth interviews with traditional leaders, community members, and youth, as well as analysis of various Mandailing cultural documents. The findings reveal that Bagas Godang and Sopo Godang are not merely historical buildings but also serve as social educational symbols rich in moral values such as mutual cooperation, deliberation, respect for elders, responsibility, and togetherness. Their role within the customary structure holds educational meaning that can be integrated into both formal and non-formal education systems as a medium for instilling national character. Thus, preserving the values embedded in Bagas Godang and Sopo Godang through value-based education is an essential step in maintaining the cultural identity of the Mandailing community and strengthening the moral foundation of the younger generation amid the challenges of globalization